Scientia Vinces: A Political-Educational Project in the Creation of the University Of São Paulo (1934) - Tavares Magalhães, Ana Paula (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
The founding of the University of São Paulo in 1934 was due to a convergence of political and educational projects in a particularly complex context in the history of Brazil. On the one hand, there were several intellectuals who had proposed the reformulation of education in the country for the preceding decade; on the other hand, a political rupture in the Brazilian Republic caused the reorganization of power. The motto Scientia vinces—Through science you will win—synthesizes, at the same time, an aspiration for knowledge as an instrument of personal and social growth, as well as the desire to enable the triumph of political groups who had been militarily defeated. As a backdrop to this political scene, one can identify aspects of modernity that reached the country in the first decades of the twentieth century: mechanization of productive activities, industrial production, urbanization, and cultural manifestations.